Agricultural commercialization and nutrition: Evidence from smallholder coffee farmers - van Asselt, Joanna; Useche, Pilar (Elsevier, 2022)
Agricultural commercialization, or the transition from growing crops for home consumption to growing some or all crops for sale, enables farmers to earn cash income that they can use to buy food in markets. This additional income may enable smallholders to purchase more healthy and/or unhealthy calories in the market, impacting their nutrition. While previous studies have examined the impact of commercialization on undernutrition, this study analyzes the impact of commercialization on overweight and obesity. Survey data from smallholder coffee farmers in rural Guatemala is used to estimate the impact of commercialization on body mass index for male and female household heads. Additionally, we explore the different pathways through which commercialization can impact nutrition, including household calorie availability, crop production, income, and gender. The empirical analysis employs an instrumental variable approach to control for endogeneity issues. Our estimation results suggest that commercialization, both in general and through dependence on coffee, leads to overweight and obesity in more commercialized households. Further, our analysis shows that while there is no relationship between commercialization of crops in general and household calorie availability, coffee dependence lowers household calorie availability. We also find that coffee dependent households decrease their production diversity and do not earn more agricultural income, both of which may negatively contribute to their nutrition. As rural areas become increasingly integrated with markets, understanding the transmission channels between agricultural commercialization and nutrition is critical.